Copper(ii) incorporated functionalized polystyrene catalyzed N-arylation of amides under solvent free condition with broad substrate scope. Issue 111 (17th November 2016) - Islam, Md. Mominul; Halder, Mita; Roy, Anupam Singha; Chatterjee, Sauvik; Bhaumik, Asim; Islam, Sk. Manirul
Abstract : A new polymer supported Cu(ii ) catalyst has been reported for N -arylation of various amides with aryl halides under neat reaction conditions. Abstract : We demonstrate here, a new polystyrene supported Cu(ii ) catalyzed proficient synthetic methodology for the facile N -arylation of aromatic, aliphatic, cyclic and heterocyclic amides with aryl halides under neat conditions. The catalyst, PS–Cu(ii )–ala, was prepared through the grafting of copper metal on a polystyrene-β-alanine imine network. The catalyst shows a wide range of substrate scope and excellent functional group tolerance, and produces the desired anilides in mostly high yields. The material is thoroughly characterized by DRS-UV, FT-IR, AAS, FE-SEM, TGA analysis and energy dispersive X-ray (EDX) studies. The catalyst can be easily recovered from the reaction medium and reused without significant loss of its catalytic activity suggesting future potential of this catalyst.